THE RELATIONSHIP BETWEEN RELIGION AND THE STATE: DISCOURSE ANALYSIS OF RELIGIOUS COMMUNICATION IN THE PUBLIC SPHERE - Ligawan, Andry Saputra (Universitas PGRI Sumatera Barat, 2023)
This study examines the relationship and relevance between religion and the state, focusing on the contribution of religion in encouraging religious participation in the public sphere amid the lack of religious contribution in the public space. The study's main objective is to identify the main patterns in the discourse to elaborate their impact on the dynamics of the relationship between religion and state. The research findings provide an in-depth understanding of how religious communication affects people's perceptions of religious values in the context of state legal and policy frameworks. This research recognizes that a better understanding of these relationships can lead to improved policies and more effective approaches to communication between religion and state. Efforts were made to build harmony between religious values and the demands of society in the country. The implications of the research include measures to prevent religious apathy towards state life, with the hope that they will play an active role, including in electoral activities that are an integral part of participation in state life. Therefore, this study details how the role of religion can enrich and deepen the interaction between religion and state, creating the basis for the positive involvement of religious people in the democratization process.